FILSAFAT PERENNIAL: MELACAK TITIK TEMU AGAMA AGAMA DAN KRISIS HUMANISTIK - Rani, Yen Fikri (Nurani, 2019)
The marginalization of human existence in modern times causes decadence and humanistic fallout, so that people forget about themselves and their primordial promises with God. As a result of this declaration, humans seem to be more inclined to mix themselves into the world without direction rather than asking for their self. Humans are lulled by false and worldly offerings that glorify the sharpness of their ratios and logic, modern and sophisticated technological devices, as if they are able to answer all human needs, so they assume there is no need for God to be in him. This condition causes people to feel empty and lose their orientation in life, so they seek speculative solutions to answer the problem. Therefore it is necessary to look again at an idea that seeks to provide an alternative offer to the suffering experienced by modern humans, namely in the form of a shared metaphysical idea that all major world religions have known better known as perennial philosophy. Perennial philosophy explains the meeting of religions by recalling the primordial message of religions, while providing an alternative solution to the spiritual crisis that has hit modern humans who have ignored religious messages.